Reduction of Total Dissolved Solids (TDS) in Tapioca Industrial Wastewater Using the Fine-Bubble Aerator Method - Jhon Hanan Sipakkar; Restiara Winada; Nadinda Siti Rosyidah; I Ketut Buyut Suratnata; Windia Hanifah (Politeknik ATK Yogyakarta, 2025)
Indonesia, the world's largest cassava producer, has substantial potential in the tapioca industry, with major production centers in Lampung, South Sumatra, and Central Java. However, the industry also generates acidic wastewater with high Total Dissolved Solids (TDS), posing environmental risks. This study evaluates the effectiveness of fine-bubble aeration in reducing TDS and stabilizing pH in tapioca industrial wastewater. Aeration was carried out at airflow rates of 2 and 5 L/min for up to 60 minutes. Results showed a significant TDS reduction from 1650 mg/L to 1000–1100 mg/L and a pH increase from 1.8 to 6.0–6.4. The 5 L/min rate achieved faster improvements. The findings suggest that fine-bubble aeration enhanced flocculation, oxidation of organic compounds , and the release of dissolved gases, providing an efficient, economical, and environmentally friendly approach for tapioca wastewater treatment.